Ultralow thermal conductivity and high-temperature thermoelectric performance in n-type K₂.₅Bi₈.₅Se₁₄ - Luo, Zhong-Zhen (2022)
We studied the narrow bandgap (0.55 eV) semiconductor K2.5Bi8.5Se14, as a potential thermoelectric material for power generation. Samples of polycrystalline K2.5Bi8.5Se14 prepared by spark plasma sintering exhibit exceptionally low lattice thermal conductivities (κlat) of 0.57 − 0.33 Wm−1K−1 in the temperature range of 300 − 873 K. The physical origin of such low κlat in K2.5Bi8.5Se14 is related to the strong anharmonicity and low phonon velocity caused by its complex low-symmetry, large unit cell crystal structure and mixed-occupancy of Bi and K atoms in the lattice. High-resolution scanning transmission electron microscopy (HRSTEM) studies and micro-analysis indicates that the K2.5Bi8.5Se14 sample is a single phase without intergrowth of the structurally related K2Bi8Se13 phase. The undoped material exhibits n-type character and a figure of merit (ZT) value of 0.67 at 873 K. Electronic band structure calculations indicate that K2.5Bi8.5Se14 is an indirect bandgap semiconductor with multiple conduction bands close to the Fermi level. Phonon dispersion calculations suggest K2.5Bi8.5Se14 has low phonon velocities and large Grüneisen parameters that can account for the observed ultralow κlat. The degree of n-type doping can be controlled by introducing Se deficiencies in the structure providing a simple route to increase the ZT to ~1 at 873 K.